2003
DOI: 10.1053/ejvs.2002.1923
|View full text |Cite
|
Sign up to set email alerts
|

An audit of out of hours interventional vascular radiology

Abstract: in a unit performing a large number of angiograms only a small number of patients require out of hours emergency angiography and interventional vascular procedures. Our impression is that this is the result of a flexible and responsive in hour's service. At the present time extra-hospital referrals do not appear to generate large amounts of out of hours work. This level of out of hours activity has implications in the provision of vascular radiological services in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…4,6 The response to the Royal College of Radiologists' plea for audit 3 has been disappointing except for two studies, which achieved conflicting conclusions. A vascular team from Leeds reviewed their vascular radiology database and found that only a small proportion (1.6%) of diagnostic arteriograms and interventional vascular procedures for limb ischaemia were required out of hours and less than half of those patients proceeded to surgery.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…4,6 The response to the Royal College of Radiologists' plea for audit 3 has been disappointing except for two studies, which achieved conflicting conclusions. A vascular team from Leeds reviewed their vascular radiology database and found that only a small proportion (1.6%) of diagnostic arteriograms and interventional vascular procedures for limb ischaemia were required out of hours and less than half of those patients proceeded to surgery.…”
Section: Discussionmentioning
confidence: 99%
“…A vascular team from Leeds reviewed their vascular radiology database and found that only a small proportion (1.6%) of diagnostic arteriograms and interventional vascular procedures for limb ischaemia were required out of hours and less than half of those patients proceeded to surgery. 4 For many NHS Tr usts the cost of providing such a comprehensive on-call vascular service may prove prohibitive and indeed the out-of-hours element of 24-hour vascular radiology cover may not be cost-efficient. But this low volume of emergency work may be underestimated as a group of vascular radiologists from Manchester have argued, 7 presenting a different experience of cross-site vascular radiology on-call service covering two vascular centres.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found a high utilization frequency (92 procedures during 12 months) of the OOHR, especially when comparing this number with that of the "ad hoc" service during the year prior to launching the OOHR for IR procedures (approximately double the number). In this context we find it important to highlight that we used strict criteria to define on-call procedures as described before [19]: only if the interventionist on call had been called in for a procedure did we define the procedure to have been undertaken "out-of-hour", as outlined in • " Fig. 1.…”
mentioning
confidence: 99%
“…We read the paper by Surash et al 1 detailing the out-ofhours vascular radiology workload in Leeds with interest. We have just completed a prospective audit of our experience in Manchester and would like to make a few comments.…”
mentioning
confidence: 99%